2022
DOI: 10.1002/jad.12085
|View full text |Cite
|
Sign up to set email alerts
|

The positive role of parental attachment and communication in Chinese adolescents' health behavior and mental health during COVID‐19

Abstract: Introduction Given that coronavirus disease 2019 (COVID‐19) has largely influenced adolescents' physical and mental health around the globe, it is important to identify protective factors that may promote adolescents' positive adjustment during the pandemic. This study aimed to examine the role of parental attachment and COVID‐19 communication in adolescents' health behavior and mental health during COVID‐19. Methods A total of 442 Chinese parent−adolescent dyads (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…50 Lastly, when parents and their children must stay at home continuously during the COVID-19 confinement, more frequent parent-child communication was associated with children's increased health behavior, reduced boredom, and decreased academic stress. 50,51 Therefore, higher parental involvement showed increased odds of having good academic performance. We found that students with higher academic self-efficacy were more likely to have good academic performance during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 98%
“…50 Lastly, when parents and their children must stay at home continuously during the COVID-19 confinement, more frequent parent-child communication was associated with children's increased health behavior, reduced boredom, and decreased academic stress. 50,51 Therefore, higher parental involvement showed increased odds of having good academic performance. We found that students with higher academic self-efficacy were more likely to have good academic performance during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 98%
“…However, the mental health status of adolescents remains concerning. During the COVID-19 pandemic, the improvement of mental health among adolescents is often accompanied by an increase in attachment security and communication with parents, continuous optimization of organizational structures within schools, and gradual adaptation to daily life changes[ 7 , 9 ]. In our study, family, school, and individual factors were considered to be influencing factors of individual depression and anxiety levels, such as family relationships, parental education level, school environment, peer relationships, and lifestyle factors[ 2 , 3 ].…”
Section: To the Editormentioning
confidence: 99%
“…Parental attachment and communication in families have increased during COVID-19 [17]. Dysfunctional parenting with low care and high control results in children's psychopathology [18]. Secure attachment and emotional closeness to parents support a healthy transition to independence and adulthood [19].…”
Section: Page 617mentioning
confidence: 99%